PENGGUNAAN ALAT PERAGA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD INPRES TASIU II, KALULU, MAMUJU PADA MATERI IPA - Arief, Siti Ni’mah; Sa’adah, Hurin Innihayatus; Sumadi, Sumadi (LPPM UNISDA, 2024)
The role of the teacher in delivering learning materials is very influential on student understanding. Teachers lack mastery of learning techniques, teachers are less competent in using learning media, cannot choose models that are in accordance with the learning theme, and the methods used are still lecture methods, often making students bored and passive when in class, so that it can reduce students' enthusiasm for learning. The purpose of this study was to determine the learning outcomes of fifth grade students by using science material props on the theme